RETRACTED: Microwave study of the effect of cold argon plasma on functional state of rat’s skin - Martusevich Andrew K.; Nazarov Vladimir V.; Surovegina Alexandra V.; Trunova Ekaterina A.; Fedotova Alexandra S. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001